2006
DOI: 10.1007/s10096-006-0168-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of serum C-reactive protein, procalcitonin, tumor necrosis factor alpha, and interleukin-10 levels as diagnostic and prognostic parameters in patients with community-acquired sepsis, severe sepsis, and septic shock

Abstract: The diagnostic value of procalcitonin, C-reactive protein, tumor necrosis factor-alpha, and interleukin-10 levels in differentiating sepsis from severe sepsis and the prognostic value of these levels in predicting outcome were evaluated and compared in patients with community-acquired sepsis, severe sepsis, and septic shock in the first 72 h of admission to the hospital. Thirty-nine patients were included in the study. The severe sepsis and septic shock cases were combined in a single "severe sepsis" group, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
79
5
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(105 citation statements)
references
References 30 publications
14
79
5
7
Order By: Relevance
“…Among the potentially useful sepsis markers, tumor necrosis factor alpha (TNF-α), interleukin 2 (IL-2), interleukin 6 (IL-6), interleukin 8 (IL-8), and interleukin-10 (IL-10) have been proposed to be the most promising candidates [1,2,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the potentially useful sepsis markers, tumor necrosis factor alpha (TNF-α), interleukin 2 (IL-2), interleukin 6 (IL-6), interleukin 8 (IL-8), and interleukin-10 (IL-10) have been proposed to be the most promising candidates [1,2,9].…”
Section: Introductionmentioning
confidence: 99%
“…They found that procalcitonin and IL-10 were more useful in discriminating between sepsis and severe sepsis, whereas TNF-α and IL-10 were more useful in predicting which cases were likely to have a fatal outcome [9].…”
Section: Introductionmentioning
confidence: 99%
“…Another study by Heper et al (2006) expressed the sensitivity and specificity for procalcitonin by 88 and 70% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, several biomarkers are being introduced. For example different types of cytokine, such as TNF-a, IL10 and CRP and also procalcitonin which are more suggested by the useful recent studies and have been able to become a head of other markers (Heper et al, 2006;Charalampos and Vincent, 2010).…”
Section: Ajidmentioning
confidence: 99%
See 1 more Smart Citation